A resonant architecture: Liam McCormick and the sonorities of place. (17th February 2018) - Martin, Daryl
Abstract: This paper discusses the work of Liam McCormick, an architect whose buildings are principally found in the landscapes of the North-West of Ireland. Primarily known for designing church buildings in the post-war period, his work is memorable for its translation of aspects of Modernist architecture within the specificities of the towns, country and coastlines of Derry and Donegal. This paper uses several of his buildings as the means to bring traditions of phenomenological approaches towards landscape into dialogue with each other. It does so in order to make connections with Jean-Luc Nancy's philosophy of subjectivity, where the aim is to move from notions of the phenomenological subject to the resonant subject. In this paper, I work with this vein of theory and transpose it into thinking about architecture, its apprehension and its enactment within its surrounding spaces.